Impact of geography on Scottish cancer diagnoses in primary care: Results from a national cancer diagnosis audit. (June 2020) - Murchie, Peter; Adam, Rosalind; Khor, Wei Lynn; Smith, Sarah; McNair, Emma; Swann, Ruth; Witt, Jana; Weller, David
Highlights: Rural patients had more cancer alarm features at first presentation. Rural patients had more pre-referral consultations and blood tests. Rural GPs were more likely to perceive they caused avoidable delays for patients. Prolonged diagnostic pathway delays were not more likely four rural patients. In Scotland rurality does not appear to delay cancer diagnosis or treatment. Abstract: Background: A recent meta-analysis of global research found cancer patients living in rural locations are 5% less likely to survive than their urban counterparts, a survival disadvantage that has never been satisfactorily explained. Aims: [1] To describe and compare primary-care involvement in the diagnosis of cancer between rural and urban patients in Scotland. [2] To compare the length of key diagnostic pathway intervals between rural and urban cancer patients in Scotland. Methods: Participating GPs in the Scottish National Cancer Audit of cancer diagnosis (2017) collected data from primary-care medical records on the diagnostic pathway of patients diagnosed in 2014. Residential postcodes designated the patients as rural or urban dwellers. Key cancer diagnostic pathway intervals (primary, diagnostic, secondary, and treatment) were compared using binary logistic regression. Descriptive analysis included comparison of patient characteristics, and routes to diagnosis. Results: 73 Scottish general practices provided data on 1, 905 cancer diagnoses. Rural patients did not have higher odds of prolonged diagnostic intervals compared to urban patients but were significantly more likely to have had a cancer alarm feature at presentation and three or more primary-care consultations prior to referral. Rural GPs were significantly more likely to perceive an avoidable delay in their patient's diagnostic pathway. Conclusion: There was no evidence that rural patients were more likely to be subject to prolonged cancer diagnostic delays than urban patients. Rural patients may experience primary care differently in the lead-up to a cancer diagnosis. The effect on outcome is probably negligible, but further research is required to confirm this.